Coastal subsistence and settlement at the Hane dune site, Ua Huka (Marquesas Islands): New insights from Pacific rat (Rattus exulans) stable isotope analysis. (October 2017) - Swift, Jillian A.; Molle, Guillaume; Conte, Eric
Abstract: The Pacific rat ( Rattus exulans ) is a small commensal omnivore; its close association with humans throughout Polynesian prehistory suggests that dietary change in this species can provide insight into localized trends in site ecology and activity. Carbon and nitrogen stable isotope analysis was applied to archaeologically recovered Pacific rat remains from recent re-excavations of the Hane dune site, Ua Huka Island (Marquesas Islands) to investigate prehistoric patterns of human subsistence and site use. Our results indicate that early subsistence at Hane was marine-oriented and focused on exploitation of high trophic level marine carnivores including offshore fish and seabirds. A rat dietary shift in later prehistory (Phase III) points to greater investment by Marquesan people towards terrestrial arboriculture and animal husbandry, as well as to restriction of fishing practices to largely inshore exploitation. These results provide a new line of evidence towards interpreting the archaeofaunal record at Hane. Stable isotope analysis of small commensal species complements archaeofaunal and ethnographic data to provide further resolution to localized patterns of site use and subsistence practices. This analysis advances a low-impact method for investigating past environments and human activity. Highlights: Stable isotope analysis (δ 13 C and δ 15 N) was applied to Pacific rat remains from the Hane dune site. Rat diet shifts from early inputs of marine resources to greater reliance on terrestrial foods. Rat stable isotopes help interpret changes to human subsistence and site activity at Hane.